Effect of "El Niño 1997-98" event in the development of Ismene amanea es (Amaryllldaceae, Liliopsidae) - Agüero, Silvia (1999)
The beginning of humidity months in the "lomas" is in June, in normal climatic conditions. The bulblet species Ismene amanea es is one of the first in germinate in relation to others herbaceous species, that is the reason it is considered an indicator of the beginning of humidity in the "lomas". The present work achieved in National Reserve of Lachay, Prov. Huaura, Dpto. Lima, present records among July of 1997 and May of 1998. The periodic evaluation in situ of seedlings let to determine the foliage area variation, number of leaves, diameter and high ofthe bulb neck. Also, it was quantified the soil humidity. The cycle phase was registered in adult plants. A relation of humid months delay in "lomas" (August of 1997) and its last until 1998, was made. The fluctuating temperature and humidíty recorded during "El Niño" had a consequence in rapídly development of specimens. The seedlings showed the bigger foliage area at the beginning of September (83,9 cm2 by plant) and was diminishing through October in direct relation with soil humidity. The 30% of adults plants flowered and only 40% of these complete the fructification, diminishing their capacity of sexual spread out. The increase of soil humidity, in the following months, did not have influence in germination of the plant against others species which restart or extended their cycle.